Existence of the transformation operator by the decomposition method - Koyunbakan, Hikmet; Bulut, Niyazi (My University, 2005)
In this article, we solve a problem obtained by the transformation operator using the decomposition method. We give the components of K(x, t) nucleus function and their numerical results, partially, when q(x) potential function is a special function (hydrogen atom and solution of the KdV equation …). © 2005, Taylor & Francis Group, LLC.
Keywords: 2000 Mathematics Subject Classifications: 34B24; 31A25; 35L20; Bessel equation; Decomposition method; Hyperbolic problem